Bridge : a novel of suspense - Beukes, Lauren (Mulholland Books/Little, Brown and Company, 2023)
"Twenty-four-year-old Bridge is paralyzed by choices: all the other lives she could have lived, the decisions she could have made. And now, who she should be in the wake of her mother's unexpected death. Jo was a maverick neuroscientist fixated on an artifact she called the "dreamworm" that she believed could open the doors to other worlds. It was part of Jo's grand delusion, her sickness, and it cost her everything, including her relationship with her daughter. But in packing up Jo's house, Bridge discovers Jo's obsession hidden amongst her things. And the dreamworm works, exactly the way it's supposed to, the way Bridge remembers from when she was a little girl. Suddenly Bridge can step into other realities, otherselves. In one of them, could she find out what really happened to her mother? What Bridge doesn't know is that there are others hunting for the dreamworm--who will kill to get their hands on it" --